Luci e ombre nella disciplina delle prescrizioni amministrative dei reati ambientali - Zampini, Andrea (Cultura giuridica e diritto vivente, 2016)
[Lights and shadows in the regulation of administrative prescriptions of environmental crimes] The Law no. 68/2015 made several amendments to the italian environmental penal regulation. This paper analyzes the new Part Six bis of the legislative decree no. 152/2006, which contains the mechanism of administrative prescriptions intended to "repair" the consequences of the contraventions contained in the decree. At the same time, the new regulation creates a special cause of extinguishment of offence for those who accomplishes the mentioned administrative prescriptions. Moreover, in this work are examined the questions of compliance of this legal regulation with the Constitution, even through some court case.